STRUCTURAL IDENTIFICATION OF ISOLATED MOLECULES OF PARKIA BIGLOBOSA (MIMOSACEAE) A PLANT USED IN TRADITIONAL MEDICINE IN BENIN - TOKOUDAGBA, Kossi Jean-Marie Denis; HOUNGBEME, GOUTON ALBAN (My University, 2022)
This study was undertaken in the perspective of contributing to the valorization of the plants of the Beninese flora. To do so, we isolated and purified by a series of chromatographic methods two pure compounds M1 and M2 from the fraction of ethyl acetate of the hydro ethanolic extract of the dried leaves of Parkia biglobosa (Mimosaceae). The spectrometric analyses carried out, namely mass spectrometry, magnetic resonance of the proton and carbon, allowed the identification of the two molecules which are all acids. These are 4-methoxybenzoic acid (anisic acid) and 5-O-(3,4-dihydroxycinnamoyl) -L-quinic acid (chlorogenic acid) respectively M1 and M2. The added value of this work lies in the fact that these two molecules have never been identified before in this plant and therefore constitute an avenue for the development of a therapeutic arsenal to fight recurrent microbial infections
Keywords: Parkia biglobosa (Mimosaceae); Isolation; Chromatographic; Methods; Spectrometric analysis